Hirudotherapy for limb ischemia in the pediatric intensive care unit: A retrospective observational cohort - Resch, Joseph C.; Hedstrom, Rachel; Steiner, Marie E.; Said, Sameh M.; Somani, Arif (Frontiers in Pediatrics, 2023)
Background: Acute limb ischemia due to microvascular malperfusion may be refractory to initial therapies. Medicinal leech therapy (hirudotherapy) has been attempted in plastic and reconstructive surgery to improve venous congestion in ischemic flaps; however, there are minimal reports related to ischemia secondary to arterial malperfusion. We evaluated a pediatric cohort from an academic intensive care unit with refractory limb ischemia in whom hirudotherapy was attempted in order to elucidate its use and outcomes. Method: Institutional patient database was queried to identify pediatric patients (<18 years) who received hirudotherapy in the pediatric critical care unit and met inclusion/exclusion criteria. Patient charts were evaluated for indices including demographics, primary disease, coagulative status, vascular access, vasoactive medication dosing, bleeding, leech use, limb and mortality outcomes. Data was evaluated to identify trends or suspected impact on outcomes. Results: Hirudotherapy was used in 7 patients for limb ischemia, 5 with congenital heart disease, and 2 others with viremic shock. Time to leech application following recognition of ischemia averaged 3 days, with duration of use averaging 3.9 days. Five patients discontinued therapy due to bleeding. Mortality rate was 57%, all secondary to multiorgan failure. In 3 surviving patients, 4 of 5 treated limbs resulted in at minimum partial amputation. Vasoactive-inotropic score tended higher prior to leech application, suggesting a vasoconstrictive pathway for arterial malperfusion. No identifiable trends appeared associated with salvaged limb or severest adverse effects. Blood loss predictably increased with leech application, as did total transfusion requirement. Conclusion: This case series establishes baseline data for use of hirudotherapy in critically ill children with acute limb ischemia caused by arterial malperfusion. Based on this retrospective cohort of critically ill children, we cannot recommend routine use of hirudotherapy for acute limb ischemia from arterial malperfusion in the pediatric intensive care unit. Application of leeches should be aligned with a protocol defining start and stop parameters, standardized leech utilization, and monitoring for adverse outcomes. Future study would benefit from consensus definitions of study outcomes, including perfusion recovery, tissue/limb salvage and bleeding manifestations. Additional prospective studies are needed prior to any standard or systematic recommendations for use.